Lama Penyimpanan Daging Ayam Broiler Terhadap Kualitasnya Ditinjau Dari Kadar Protein Dan Angka Lempeng Total Bakteri - Insun Sangadji; Jurianto Jurianto; Muhammad Rijal (BIOSEL (Biology Science and Education): Jurnal Penelitian Science dan Pendidikan, 2019)
This study aims to determine the effect of storage time of broiler chicken on its quality in terms of protein content and total bacterial plate number. This research was conducted on 11-19 December 2017. The design used in this study was a Completely Randomized Design (CRD) with 3 treatments consisting of 2 days of storage (A1), 4 days (A2) and 6 days (A3) and the number of replications is 3 replications. Data were analyzed using ANOVA. Sample analysis was carried out in the MIPA laboratory at the Faculty of Tarbiyah and Teacher Training, Ambon IAIN and Pattimura University Basic Chemistry Laboratory. The results showed that there was an effect of the length of storage of broiler chicken on protein levels and total bacterial plate numbers. The effect of broiler chicken meat storage on protein content was 14.2% while the effect of broiler chicken storage on the total plate number of bacteria was 12.7%. Key Words: Duration of Storage, Broiler Chicken Meat, Protein Levels, ALT